CLUSTERING KESEHATAN LINGKUNGAN BERDASARKAN PARAMETER SARANA AIR BERSIH DENGAN K-MEDOIDS - Sodik Kirono (Jurnal Digit, 2018)
Abstract Enviromental health is one of the most important aspect in public health. But, data and report in departement od health of Cirebon district have not been analyzed properly. This research is conducted to analyze enviromental health data in Cirebon in clean water facilities parameter. This parameter is choosen because water is basic needs and Cirebon is one of district that has problem about it. Its like limitations of ground water reserves, sea water intrusion, and water management by PDAM has not optimal yet. This research will analyze group of enviromental health in Cirebon disctrict. The research is begin with data collection, data preprocess, clustering with k-medoids algorithm, analyze and visualize cluster. The research show that the difference between cluster is in sumur gali (SGL), sumur pompa tangan dangkal (SPT DKL), sumur pompa tangan dalam (SPT DLM). and PDAM attribute. Analysis process is conducted by observe each cluster medoids. First cluster is group of sub district that access to clean water by SPT DLM at highest value around 7%, both SGL and SPT DKL around 28%, and there is access to PDAM at around 2%. Second group is group of sub district that access to clean water by SPT DKL at highest value around 55%, SGL around 30%, while access to SPT DLM and nearly zero percent access to PDAM. Third group is group subdistrict that access to clean water by SGL at highest value around 64% and PDAM 5%, access to SPT DKL around 16%, and nearly zero access to SPT DLM. Plotting of cluster in maps shown that neighboring subdistrict tend to show same cluster (color), except several subdistrict, so it needs to be futhermore analyzed with other indicators like geography, demography, and social-economy. Keywords: Cirebon, clean water facilities, clustering, environmental health, k-medoids